FLORA AND PHYTOCOENOSES OF THE PRE-NAREV PLEISTOCENE, BELARUS - Yakubovskaya T.V.; Krutous E.A. (My University, 2003)
Based on carpological data, the composition and evolution of flora and phytocoenoses that existed in Belarus from the initial Pleistocene to the pre-Narev glaciation are analyzed and peculiarities of transformation of the late Pliocene flora into the glacial Pleistocene one are outlined. The analysis of the climatic affinity of flora and phytocoenoses and their evolution revealed the Vselyub Cryochron, El'nya Thermochron, Zhlobin Cryochron, and Rogachev Thermochron in the Early Pleistocene (Eopleistocene) succession of Belarus. The pre-Narev interval of the Middle Pleistocene is shown to comprise the Varangian Cryochron (glaciation) and Ruzhany Thermochron (interglacial). Substantial changes in the flora composition, particularly in the relict group, have been related to the Varangian glaciation and are recorded across the Early-Middle Pleistocene boundary.
Keywords: Belarus; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен